Can 0.5% Sodium Hypochlorite Treat Candida-Associated Denture Stomatitis? - de Freitas-Fernandes, Frederico Silva (2024)
Objective: To evaluate a 0.5% sodium hypochlorite (SH) protocol in reducing Candida spp. levels in complete dentures (CD) and palate and denture stomatitis (DS) remission. Material and Methods: Twelve CD wearers diagnosed with Candida-associated denture stomatitis (CADS) had their initial situation (Candidaspp. levels and DS score) recorded (baseline). Then, participants were instructed to soak dentures once a day (10 minutes) in 0.5% SH. Candida spp. levels and DS scores were reassessed after 15, 30, and 60 days of SH denture cleanness. Biofilms from the denture base and palate were seeded in CHROMagar Candida. After incubation, colony-forming units were calculated. The palate was photographed at each time point, and DS was assessed according to Newton's classification. Data of Candida spp. levels were analyzed by 2-way repeated measures ANOVA followed by the Holm-Sidak test, and DS scores data were accessed by Friedman's 2-way ANOVA by ranks (α=0.05). Results: 0.5% SH significantly reduced Candida spp. levels after treatment compared to baseline (p<0.001) for both sites. Although at baseline, Candida spp. counts were higher on the denture base (p<0.001), no significant differences were observed between the collected areas within the other time points (p<0.05). Also, 0.5% SH effectively reduced clinical signs of DS after treatment (p<0.05). Conclusion: The protocol tested effectively decreased Candida spp. levels on the denture base and palatal mucosa and effectively reduced the signs of DS.